2003
DOI: 10.1016/s1010-7940(03)00440-8
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of stroke after coronary artery bypass grafting

Abstract: Although occurrence of CVA seems mainly related to preoperative comorbidities, perioperative surgical variables, such as off-pump surgery, myocardial ischemia and cardiopulmonary bypass time, do not seem to independently influence CVA rate after CABG. In this regard CVA prevention should be performed before posing an indication to CABG, and closer evaluation of patients' risk profiles and tailored clinical/surgical strategies for those patients at higher risk for CVA occurrence should be included.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 17 publications
3
30
0
1
Order By: Relevance
“…The reported frequencies range between 1% and 4% in patients undergoing coronary artery bypass grafting (CABG), with the risk nearly doubled in older age. [1][2][3][4][5] Similar rates were found for patients receiving heart valve replacement. 6,7 Cognitive deficits after heart surgery have been observed in 33% to 83% of patients during the first weeks after surgery.…”
mentioning
confidence: 70%
“…The reported frequencies range between 1% and 4% in patients undergoing coronary artery bypass grafting (CABG), with the risk nearly doubled in older age. [1][2][3][4][5] Similar rates were found for patients receiving heart valve replacement. 6,7 Cognitive deficits after heart surgery have been observed in 33% to 83% of patients during the first weeks after surgery.…”
mentioning
confidence: 70%
“…This decrease was attributed to hypothermia and hypocarbia. In a study conducted by D'Ancona et al [11], as documented, the carotid artery disease and history of previous stroke can result in CVA through intraoperative or perioperative cerebral hypoperfusion. We have examined other variables, such as pump time, cross-clamp time, perfusion pressure and flow, during coronary bypass surgery among our three groups to find any association with perioperative stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Its etiology is multifactorial, including cerebral embolization from iatrogenic mobilization of atherosclerotic plaques, air/fat embolism, peripheral vascular disease (PVD), hemodynamic fluctuations, cerebral hyperthermia, aortic dissection, particular microemboli, emboli because of aortic arch disease, aortic "crunch" occurring with cross-clamping or cannulation, air and fat emboli [7][8][9][10] and systemic inflammatory reaction [11]. In spite of that, concomitant carotid artery disease may be very important in the etiology of perioperative stroke in patients undergoing CABG.…”
Section: Introductionmentioning
confidence: 99%
“…Percentage varies across studies and depends on study design, patient risk proile, operative techniques, and the length of study followup. Although advances in surgical and medical management have occurred across the last 10 years, the risk of stroke after coronary artery bypass grafting (CABG) has not signiicantly declined likely because of the progressive aging of the CABG population [4].…”
Section: Introductionmentioning
confidence: 99%
“…Percentage varies across studies and depends on study design, patient risk proile, operative techniques, and the length of study followup. Although advances in surgical and medical management have occurred across the last 10 years, the risk of stroke after coronary artery bypass grafting (CABG) has not signiicantly declined likely because of the progressive aging of the CABG population [4].The etiology of postoperative stroke is multifactorial. Previous studies showed that the risk factors for postoperative stroke following CABG include age, low left ventricular ejection fraction, unstable angina, atherosclerosis of the ascending aorta, chronic renal failure, chronic obstructive pulmonary disease, calciied aorta, a history of previous stroke, carotid stenosis, duration of cardiopulmonary bypass, peripheral vascular disease, smoke, and diabetes mellitus.…”
mentioning
confidence: 99%